Implementasi Fitur Sleeping Client Pada Protokol Message Queue Telemetry Transport - Sensor Network (MQTT-SN) Berbasis Arduino & NRF24L01 - Yandra Charlos Hasugian; Sabriansyah Rizqika Akbar; Kasyful Amron (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
WSN (Wireless Sensor Network) is a connection contained sensor node or actuator, gateway, and client. WSN can be implemented using Message Queue Telemetry Transport (MQTT) is a protocol that runs on TCP/IP, where the sensor node connected to the server through the gateway as an intermediary client and server. Message Queue Telemetry Transport - Sensor Network (MQTT-SN) is way to solve the problem. In MQTT-SN have a feature that used to make a move client's state is Sleeping Client. In feature sleeping client there are several states are active, disconnect, asleep, awake, and lost. System in this research there are 2 client which consists of microcontroller Arduino Nano, module of NRF24L01, and sensor. And a gateway which consists of microcontroller Arduino Nano and module of NRF24L01. Client devices will search a gateway for communicate with gateway, after connect with the gateway, client will send data sensor and messages for changes states in sleeping client feature. Result from testing of system, client succeed to changes states and can send data sensor use a client device and a gateway device although use 2 client devices and a gateway device.